From Diversity Ideologies to the Expression of Stereotypes: Insights Into the Cognitive Regulation of Prejudice Within the Cultural-Ecological Context of French Laïcité - Lankester, Lucie-Anna; Alexopoulos, Theodore (Frontiers in Psychology, 2021)
This theoretical paper examines the context-sensitivity of the impact of cultural norms on prejudice regulation. Granting the importance of understanding intergroup dynamics in cultural-ecological contexts, we focus on the peculiarities of the French diversity approach. The major cultural norm, the Laïcité (i.e., French secularism) is declined today in two main variants: The Historic Laïcité, a longstanding egalitarian norm coexisting with its amended form: The New Laïcité, an assimilationist norm. In fact, these co-encapsulated Laïcité variants constitute a fruitful ground to cast light on the processes underlying prejudice regulation. Indeed, it is documented that the assimilationist New Laïcité is linked to higher levels of prejudice as compared to the egalitarian Historic Laïcité. To this day, research mainly explored interindividual determinants of Laïcité endorsements and specified how these endorsements shape prejudice. Crucially, this “indirect-endorsement path” does not account for the more straightforward causal relationship between Laïcité and prejudice. Moreover, recent experimental evidence suggests that the normative salience of both Laïcité norms shape intergroup attitudes beyond personal endorsement. Therefore, in this contribution, we complement previous work by investigating the possible socio-cognitive processes driving this “direct-contextual path”. In doing so, we seek to bridge the gap of causality by investigating how the Laïcité norms can set the stage for specific regulatory strategies. Our reasoning derives from an application of the Justification-Suppression Model bolstered by classical work on mental control, modern racism and diversity ideology. From this, we sketch out the operative functioning of two distinct regulation processes: a) one that prevents prejudicial attitudes but which can have unexpected consequences on stereotyping within the Historic Laïcité context (i.e., suppression) and b) one that helps realize prejudice within the New Laïcité context (i.e., justification). From this analysis, we discuss the consequences for intergroup relations within and beyond the French context. In particular, we outline the importance of an adequate framing of egalitarian ideologies so that they achieve their goal to foster harmonious intergroup relations.